Tay Son uprising, 1771-1802 : reassessing Viet Nam's relations with the Malay Archipelago - Ku, Boon Dar; Azlizan Mat Enh, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article aims to elucidate the history of interactions between Viet Nam and the Malay Archipelago’s kingdoms during the Tay Son brothers’ insurrection, with a particular emphasis on how foreign relations were linked. The study also discusses the reasons for Viet Nam’s selection of the Malay Archipelago, despite the fact that Viet Nam maintained a closed-door policy with the outside world in the late 18th and early 19th centuries. This study is significant because it demonstrates the contact and connectivity between Viet Nam and the Archipelago in the early 17th century. This is because the Vietnamese have always regarded the Malay realm as a region rich in natural riches and jewels. The study employs a quantitative method to undertake a content analysis of texts, particularly original sources such as Nguyen Dynasty (Vietnam) and Qing Dynasty (China) palace documents gathered from Vietnamese and Chinese archives. The study indicated that the Malay Archipelago became the sole destination specifically mentioned by the Vietnamese people as a place of sanctuary and a place to seek assistance during their country’s economic collapse and political degradation.